Manipulating electromagnetic waves with metamaterials： Concept and microwave realizations - 何琼 孙树林 肖诗逸 李欣 宋争勇 孙午炯 周磊 (Chinese physics B, 2014)
Our recent efforts in manipulating electromagnetic （EM） waves using metamaterials （MTMs） are reviewed with em- phasis on 1） manipulating wave polarization and transporting properties using homogeneous MTMs, 2） manipulating surface-wave properties using plasmonic MTMs, and 3） bridging propagating and surface waves using inhomogeneous meta-surfaces. For all these topics, we first illustrate the physical concepts and then present several typical practical real- izations and applications in the microwave regime.